Mediações pedagógicas nas práticas alfabetizadoras - Ribeiro, Ana Claudia Gonçalves (2006)
The following study, developed in the Education Master s Degree course, is part of the researching field of Curriculum, Teaching and School Practices aims at comprehending the pedagogical mediations practiced in literacy classes, from the understanding of the theoretical conceptions that surround such practice. The context in which the research was conducted is an elementary school context, which integrates the Municipal Teaching System of Santa Maria- RS; such school is located at the margin of the city. The subjects who took part and were involved in the research were two elementary school teachers involved in literacy and their groups, where observations on the pedagogical mediations took place. An ethnographical study was done based upon authors like. Ludke & André (1986), Altet (2000), Bogdan (1986), Bolzan (2001), Engers (1994) e Werstsch (1995); and the data was collected from the direct observation of the 1st grade groups activities, of semi-structured and open interviews with the groups teachers, and the study of the school Political Pedagogical Project, as well as its regulations. The research results enabled some comprehension on the pedagogical mediations practiced by the literacy teachers in different situations of the classroom environment. Throughout the analysis, it was highlighted, categories that illustrate such process. These categories were presented as: reflected pedagogical mediations, quotidian pedagogical mediations and improvised pedagogical mediations. It was perceived, although, that the quotidian mediations were strongly present in the participant teachers teaching literacy practices. In the conducted analysis, it is possible to affirm that the found pedagogical mediations focus on the types of intervention in which the teacher will be able or not to think about the action, will be able or not to previously plan, will organize the school work and reflect upon his/her mediation on the students learning process. The teacher has the responsibility of retaking his/her ideas and conceptions from his/her reflection over the action and reaction.